Policy implementation of midwife traditional birth attendant partnerships to reduce maternal and child mortality - Nawir Rahman (Edukasi Ilmiah Indonesia, 2025)
Introduction: Maternal and child mortality remains a critical public health challenge in Indonesia, particularly in rural areas where access to formal health services is limited. In Kabupaten Takalar, traditional birth attendants (dukun) continue to play a central role in childbirth practices. To address this issue, the local government implemented a partnership policy between midwives (bidan) and dukun aimed at improving maternal and neonatal outcomes through culturally sensitive collaboration. Methods: This study employed a mixed-methods design to assess the effectiveness of the bidan–dukun partnership policy. Quantitative data were obtained from maternal and child mortality statistics, program coverage reports, and community surveys. Qualitative data were collected through in-depth interviews and focus group discussions with midwives, dukun, and community members. Data triangulation was applied to enhance the validity of findings. Results: The findings indicate that the partnership policy was implemented at a moderate to high level, with approximately three-quarters of targeted areas adopting the model. Community understanding of the program was relatively high, although active participation remained uneven. Quantitative trends showed a reduction in the maternal mortality ratio during the implementation period. Qualitative results revealed improved referral practices, increased trust in formal health services, and clearer role differentiation between midwives and dukun. However, challenges persisted, including cultural resistance, coordination gaps, and limited training. Conclusion: The study demonstrates that a culturally inclusive partnership between midwives and traditional birth attendants can contribute to reducing maternal and child mortality by bridging formal health systems and community-based practices. Strengthening coordination mechanisms, continuous capacity building, and community engagement are essential to maximize policy impact. These findings provide evidence to inform local and national strategies for maternal and child health improvement.